Molecular engineering tools for the development of vaccines against infectious diseases: current status and future directions - Wenhui Xue; Tingting Li; Ying Gu; Shaowei Li; Ningshao Xia (Taylor & Francis Group, 2023)
Introduction The escalating global changes have fostered conditions for the expansion and transmission of diverse biological factors, leading to the rise of emerging and reemerging infectious diseases. Complex viral infections, such as COVID-19, influenza, HIV, and Ebola, continue to surface, necessitating the development of effective vaccine technologies. Areas covered This review article highlights recent advancements in molecular biology, virology, and genomics that have propelled the design and development of innovative molecular tools. These tools have promoted new vaccine research platforms and directly improved vaccine efficacy. The review summarizes the cutting-edge molecular engineering tools used in creating novel vaccines and explores the rapidly expanding molecular tools landscape and potential directions for future vaccine development. Expert opinion The strategic application of advanced molecular engineering tools can address conventional vaccine limitations, enhance the overall efficacy of vaccine products, promote diversification in vaccine platforms, and form the foundation for future vaccine development. Prioritizing safety considerations of these novel molecular tools during vaccine development is crucial.